Methods review to study information needs of scientists and specialists - M. A. Pleshakova; T. A. Kalyuzhnaya (Библиосфера, 2017)
Users’ information needs (IN) underlying the system of information-library servicing are still actively studied by specialists of the librarianship. These studies require the correct choice of research methods. The authors attempted to analyze techniques of studying scientists’ and specialists’ IN reflected in professional publications, to find out whether there are new methods, and to determine how these techniques are transformed in a changing environment of information-library activities. Analysis of the documents reflected in DB «Informatics» by VINITI and RSCI, according to a search order of «studying information needs» showed that the range of issues on this problem is rather wide, but the most frequently discussed one is methods and methodology of studying IN. Herewith references discuss various ways of grouping IN research techniques. The authors carry on detailed analysis of these methods and interpreting the issue of their use at a theoretical level based on the research method elements allocated by V. S. Kreidenko, choosing two of them to define the technique essence, in their view. As a result, they conclude that no new method have lately appeared, but IN studying techniques traditionally used in libraries have been modified; in accordance with IN division into the objective and subjective ones, research methods can be divided into two groups as well: techniques of studying subjective IN and techniques to studying objective IN; almost all IN research methods completely or partially can be used in the electronic environment.